PENINGKATAN KETERAMPILAN BAHASA INGGRIS MASYARAKAT PEGUNUNGAN DI DESA PEMEPEK - Suryadi, Hendra; Paris, Atika Salman; Rosyidi, Ahmad Zuhri; Muttaqin, Muh. Zaini Hasanul (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
The importance of soft skills for the younger generation is the basis for the preparation of this Community Partnership Program (PKM). The focus of this community service activity is to increase the interest in learning English for the people in highlanders based on environmental/nature folklore books and to increase the soft skills of Karang Taruna partners in Pemepek Village, Pringgarata District. The specific objective of this PKM is to increase interest in learning and improve English skills (soft skills). Some of the methods used in the Community Partnership Program (PKM) are question and answer and discussion methods to identify knowledge and supporting technology. The lecture method is used during the learning process and theoretical understanding of English. The results of community service that has been trained show that learning English based on nature-themed storybooks is easier to understand by the students being taught. By using this method, there is a pretty good increase for students. Apart from that, other results obtained were that youth and children absorbed English learning material more quickly and this activity was also a starting point for other activities.